Legal Analysis of the Role of Quarantine Veterinarians in the Enforcement of Criminal Sanctions for Animal Quarantine Violations in Indonesia - Nilam M. Siregar; Dwi Pratiwi Markus; Sri Yati (Rechtsnormen: Journal of Law, 2026)
The increase in global trade traffic has heightened the risk of spreading Quarantine Animal Pests and Diseases (HPHK), thereby demanding the effectiveness of the quarantine system not only administratively but also in the enforcement of criminal law. The main issue of this study is the lack of optimal understanding regarding the legal status of quarantine veterinarians and their role in the evidentiary process for animal quarantine crimes, which are of a technical-scientific nature. This study aims to analyze the legal status of quarantine veterinarians and examine their role as expert witnesses in the criminal evidentiary system. This study aims to analyze the legal status of quarantine veterinarians and their role in the process of proving animal quarantine crimes. The method used is normative legal research with a legislative and conceptual approach, supported by qualitative analysis of primary, secondary, and tertiary legal materials. The results of the study indicate that quarantine veterinarians possess attributive authority as quarantine officials under Law No. 21 of 2019, while simultaneously serving as expert witnesses whose testimony is determinative in proving the elements of quarantine offenses. The novelty of this study lies in the finding that the proof of animal quarantine offenses is expert-dependent; without the testimony of a quarantine veterinarian, the element of disease transmission risk as the core of the offense cannot be legally and convincingly proven in court. The effectiveness of quarantine law enforcement depends not only on legal norms but also on the integration of legal and veterinary scientific aspects. This study affirms that quarantine veterinarians are key actors in ensuring the success of evidence presentation and the imposition of criminal sanctions in animal quarantine cases.